Power of garbage - Nicoli Zarzar, Alberto (2015)
The article offers a personal view about the violence that begins in the family circle up to the approach of media speeches, specifically developed by Peruvian television with channels of open signal and even some proposal that cable offers us. To do this, been referenced to existing standards of regulation in Peruvian radio and television, media whose content, of low quality, there do not help to form conscious citizens of their social environment.